Point‐of‐care ultrasound‐guided pericapsular nerve group block for superior pubic ramus fracture in the emergency department: A case report. Issue 3 (3rd July 2022) - Cripps, Elinor; Fahey, Alan; Snelling, Peter James
Abstract: Pelvic fragility fractures, such as pubic ramus fractures, are a common and painful condition in the elderly population. Despite this, there are few regional anaesthesia options available to effectively relieve pain in these fracture types and avoid potential side effects from opioid administration. This case report describes an elderly patient with a superior ramus fracture, who received effective pain relief with motor sparing, using a standard‐volume point‐of‐care ultrasound‐guided pericapsular nerve group (PENG) block performed in the emergency department. The standard‐volume PENG block performed by an emergency clinician appears to be a safe, effective and feasible regional anaesthesia technique for superior pubic ramus fracture, with the additional benefit of motor sparing that may potentially facilitate earlier mobilisation and discharge.